2009
DOI: 10.1614/ws-08-131.1
|View full text |Cite
|
Sign up to set email alerts
|

In-Field and Soil-Related Factors that Affect the Presence and Prediction of Glyphosate-Resistant Horseweed (Conyza canadensis) Populations Collected from Indiana Soybean Fields

Abstract: Glyphosate-resistant (GR) crops have been rapidly adopted in the United States and the evolution of GR weeds throughout the world has also been on the rise. With experience, weed scientists and crop advisers develop “intuition” on the basis of field history and current in-field conditions for predicting whether escaped weed biotypes may be herbicide resistant. However, there are no previous reports on the association of in-field crop management factors with the prediction of herbicide resistance. By using in-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
(44 reference statements)
3
21
0
Order By: Relevance
“…The authors suggest that fitness costs may partially contribute to the relatively low frequency of glyphosate resistance alleles in the absence of selection, which is a plausible explanation. However, other studies have found minor or no fitness costs of glyphosate resistance 47–50…”
Section: Glyphosate‐resistant Weeds: History Mechanisms Genetics Anmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors suggest that fitness costs may partially contribute to the relatively low frequency of glyphosate resistance alleles in the absence of selection, which is a plausible explanation. However, other studies have found minor or no fitness costs of glyphosate resistance 47–50…”
Section: Glyphosate‐resistant Weeds: History Mechanisms Genetics Anmentioning
confidence: 98%
“…In Indiana, GR C. canadensis was associated with a lack of crop rotation diversity—i.e. soybean monoculture—and no‐tillage systems 47. The light C. canadensis seeds can disperse readily by wind or convective air currents, documented at distances of over 500 km 77, 78…”
Section: Management Strategies and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most resistant weed biotypes have other mechanisms of resistance based on gene amplification15, 16 or sequestration of glyphosate in the vacuole 17, 18. Weeds with these two mechanisms of action have been highly problematic in some places where GR crops have been grown continuously for several years, such as GR cotton in the southeastern United States19 and GR soybeans in the mid‐southern and mid‐western United States 5, 20…”
Section: Why New Herbicide Modes Of Action Are Neededmentioning
confidence: 99%
“…Although direct-mail surveys and interviews have made clear the general beliefs that underlie weed control decisions, still unknown are the specific criteria that perhaps ultimately determine whether control is implemented or withheld because surveys and interviews can occur much later in the season, and therefore, they may fail to incorporate the actual conditions seen by farmers during deliberation. Such disconnections between settings of commercial crop production and scientific inquiry have long been recognized (Thompson and Thompson 1990;Wuest et al 1999), and have recently been accounted for with paired surveys of weed communities and management practices on cooperator farms (Davis et al 2009;Luschei et al 2009). …”
mentioning
confidence: 99%